The Role of Anti-HBs in Hepatitis B Reactivation during Direct-Acting Antiviral Therapy for Chronic Hepatitis C. Issue 6 (August 2018) - Spaan, Michelle; Bruce, Matthew; Agarwal, Kosh; Carey, Ivana
Background: Hepatitis B reactivation in patients with resolved HBV can occur during hepatitis C treatment with direct-acting antivirals, but only a few cases have been described. It is not clear which patients are at risk for HBV reactivation and how to manage them. Methods: Three patients (all hepatitis B surface antigen [HBsAg]-negative, antibody to hepatitis B core [anti-HBc] positive and HBV DNA negative) experienced a late HBV reactivation 12 weeks post-treatment but were able to control their viraemia. HCV RNA, HBV DNA, anti-HBc and anti-HBs were measured in these patients and in 37 HBsAg-negative, anti-HBc positive, HBV DNA negative control patients during direct-acting antiviral therapy for chronic hepatitis C. Results: Baseline anti-HBs do not differ between patients with and without HBV reactivation. Patients with HBV reactivation, however, significantly increased their anti-HBs at time of reactivation, while patients without HBV reactivation show stable anti-HBs during therapy ( P =0.007). Conclusions: Anti-HBs might be an important marker to delineate patients at risk for clinically significant HBV reactivation.